GROUP OF GASTROCOPTA EDLAUERI (WENZ, 1921) – GASTROCOPTA CONTRACTA (SAY, 1872) (MOLLUSCA, PULMONATA) FROM THE CENOZOIC OF EURASIA - Prysiazhniuk, V.A. (Institute of Geological Sciences, NAS of Ukraine, 2019)
The comprehensive study of fossil gastropods of the G. edlaueri (Wenz, 1921) – G. contracta (Say, 1872) group from the Oligocene sediments of Mongolia, the Miocene sediments of Tuva, as well as the Neogene ones of Ukraine and Poland is presented. The Gastrocopta species of this group are considered as rather of North American than Central Asian origin. The study shows that the intraspecies categories only can be distinguished within the Gastrocopta edlaueri which demonstrates wide shell variability. A reliable study of accompanying samples of terrestrial mollusks along the collecting of fossil mammals requires the participation of malacologists to provide a complete picture of mollusk fauna of the investigated localities. The variability of G. edlaueri (Wenz, 1921) in time and space was studied in detail. It was shown that there is no sufficient basis for isolating a new species of G. polonica.